KARAKTERISTIK OPERATOR HIPONORMAL-p PADA RUANG HILBERT - Gunawan Gunawan (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2014)
This article discusses the definition and properties of p-hiponormal operators for p>0. To investigate the properties of p-hiponormal operators, the concept of positive operators, partial isometry operators, decomposition of operators, and existence of partial isometry operators for any operator on a Hilbert space are required.